Are lateral ankle injuries in children fractures or sprains?. Issue 6 (15th April 2018) - Beatty, Erica; Deschênes, Maude; Archambault, Patrick
Abstract : Clinical question: What is the prevalence of Salter-Harris type I distal fibula fractures in children with lateral ankle injuries? Article chosen: Boutis K, Plint A, Stimec J, et al. Radiograph-negative lateral ankle injuries in children occult growth plate fracture or sprain? JAMA Pediatr 2016;170(1):e154114.